Case Series about the Changed Antiplatelet Protocol for Carotid Endarterectomy in a Teaching Hospital: More Patients with Complications? - Marsman, Martijn S.; Özdemir- van Brunschot, Denise M.D.; Jahrome, Abdelkarime Kh; Veeger, Nic J.G.M.; Schuiling, Wouter J.; van Rooij, Frank G.; Koning, Giel G. (The Surgery Journal, 2018)
Introduction In the Netherlands, clopidogrel monotherapy increasingly replaces acetylsalicylic acid and extended release dipyridamole as the first-choice antiplatelet therapy after ischemic stroke. It is unknown whether the risk of peri- and postoperative hemorrhage in carotid artery surgery is higher in patients using clopidogrel monotherapy compared with acetylsalicylic acid and extended release dipyridamole. We therefore retrospectively compared occurrence of perioperative major and (clinical relevant) minor bleedings during and after carotid endarterectomy of two groups using different types of platelet aggregation inhibition after changing our daily practice protocol in our center.Material and Methods A consecutive series of the most recent 80 carotid endarterectomy patients (November 2015–August 2017) treated with the new regime (clopidogrel monotherapy) were compared with the last 80 (January 2012–November 2015) consecutive patients treated according to the old protocol (acetylsalicylic acid and dipyridamole). The primary endpoint was any major bleeding during surgery or in the first 24 to 72 hours postoperatively. Secondary outcomes within 30 days after surgery included minor (re)bleeding postoperative stroke with persistent or transient neurological deficit, persisting or transient neuropraxia, asymptomatic restenosis or occlusion, (transient) headache. Reporting of this study is in line with the ‘Strengthening the Reporting of Observational Studies in Epidemiology’ statement.Results Although statistical differences were observed, from a clinical perspective both patients groups were comparable. Postoperative hemorrhage requiring reexploration for hemostasis occurred in none of the 80 patients in the group of the clopidogrel monotherapy (new protocol) and it occurred in one of the 80 patients (1%) who was using acetylsalicylic acid and dipyridamole (old protocol). In three patients (4%) in the clopidogrel monotherapy and one patient (1%) in the acetylsalicylic acid and extended release dipyridamole protocol an ipsilateral stroke was diagnosed.Conclusion In this retrospective consecutive series the incidence of postoperative ischemic complications and perioperative hemorrhage after carotid endarterectomy (CEA) seemed to be comparable in patients using clopidogrel monotherapy versus acetylsalicylic acid and extended release dipyridamole for secondary prevention after a cerebrovascular event. This study fuels the hypothesis that short- and midterm complications of clopidogrel and the combination acetylsalicylic acid and extended release dipyridamole are comparable.
Keywords: acetylsalicylic acid; ASA; bleeding; carotid endarterectomy; carotid artery; clopidogrel; dipyridamole; complication